2019
DOI: 10.1101/819805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Electrophysiological Signature of Mind Wandering

Abstract: Mind wandering during ongoing tasks can impede task performance and increase the risk of failure in laboratory as well as in daily-life tasks and work environments. Neurocognitive measures like the electroencephalography (EEG) offer the opportunity to assess mind wandering non-invasively without interfering with the primary task. However, the literature on electrophysiological correlates of mind wandering is rather inconsistent. The present study aims towards clarifying this picture by breaking down the tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 81 publications
2
15
0
Order By: Relevance
“…Consistent with previous literature [ 52 , 30 , 53 ], we segmented the trials into early and late window to measure modulations of power over the trial. In our data, alpha and beta were more prominent after 200 ms, in line with several other studies [ 27 , 30 , 38 , 49 , 54 ]. We therefore measured these rhythms using 200−600 ms and 600−1000 ms for alpha/beta, and 0−500 ms and 500−1000 ms for theta ( Fig.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous literature [ 52 , 30 , 53 ], we segmented the trials into early and late window to measure modulations of power over the trial. In our data, alpha and beta were more prominent after 200 ms, in line with several other studies [ 27 , 30 , 38 , 49 , 54 ]. We therefore measured these rhythms using 200−600 ms and 600−1000 ms for alpha/beta, and 0−500 ms and 500−1000 ms for theta ( Fig.…”
Section: Methodssupporting
confidence: 93%
“…Beside investigations of ERPs, other studies have examined EEG spectral power during MW episodes in population-based samples. Using thought probes and quantitative EEG (qEEG) analyses, parietal alpha power increased during episodes of MW during vigilance [ 25 ], Stroop [ 26 ] and switching [ 27 ] tasks. Braboszcz and Delorme [ 28 ] investigated quantitative EEG power in a population-based sample.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, former studies demonstrated that attentional lapses and neural processing of stimuli via the occipital visual P1 are related (Baird et al, 2014;Kam et al, 2011). Also, inter trial alpha power, which reflects internally directed mental states, and which was shown to be strongly predictive for the experience of attentional lapses (Arnau et al, 2020), could not explain the WPR. Altogether, it seems that the chosen electrophysiological covariates did not account for the WPR, except for the small effect of mean theta power.…”
Section: Influence Of Covariates On the Wpr In Covariancesmentioning
confidence: 89%
“…Theta power, especially event-related frontal-midline theta power, is associated with the use of executive control and regulation processes (Cavanagh et al, 2012;Cavanagh & Frank, 2014). Previous research has suggested that theta power may decrease when attentional lapses occur and may be subsequently upregulated as a compensatory mechanism once attentional drifts are noticed (Arnau et al, 2020;Atchley et al, 2017;Braboszcz & Delorme, 2011). This redirection of attention towards the primary task may be initiated by either metaawareness regarding one's attentional state (Braboszcz & Delorme, 2011;Smallwood et al, 2007) or by external cues such as the presentation of the fixation cross or the next experimental trial (Arnau et al, 2020).…”
Section: Multiverse Manifestations and Measurements Of Attentional Lapsesmentioning
confidence: 99%
“…This is puzzling because the occurrence of mind wandering is thought to reflect a failure of executive control to defend primary-task focus (McVay & Kane, 2009, 2010, 2012), yet older adults generally have poorer executive control (for reviews, see Craik & Salthouse, 2011;Machado, 2021;McDonald et al, 2018), therefore one would expect the frequency of mind wandering to increase as people age (due to decreased executive control; Thomson et al, 2015). Furthermore, mind-wandering studies involving task-switching paradigms in healthy young adults have consistently demonstrated that switching performance is not adversely affected by mind wandering (i.e., similar reaction times were obtained for the trials leading up to "ontask" and "off-task" reports; Arnau et al, 2020;Kam & Handy, 2014;Thomson et al, 2014).…”
Section: Introductionmentioning
confidence: 91%